Physical Abuse Cases at Boarding Schools: Phenomena and Its Prevention Model - Sumawiharja, Farhan Arif; Ayu Dwi Rahmawati; Doti Sekar Medina (Sekolah Tinggi Ilmu Kepolisian, 2024)
This research elaborates factors that contribute to physical abuse cases at Boarding Schools, which explained with routine activity theory and power relation theory. Besides, this research also evaluates the Minister of Education and Culture Regulation Number 82 Year 2015 On Prevention and Countermeasures of Violence in Education Unit Environment, and Law No. 18 Year 2019 on Boarding schools. Physical abuse cases that occur at Boarding schools are caused by excessive discipline implementation. Therefore, this encourages and motivates senior boarders or boarding caretaker to commit violence. This research uses qualitative method, with a live interview held at a boarding school which experiencing physical abuse cases causing loss of life. Delphi method is also used to deepen the prevention model and generate education expert insights focusing on the educational development of boarding school. This research is unveiling the extraordinary causes of violence and resulting on validated prevention model by education experts in boarding schools.